Potensi dan Prospek Ekspor Damar Batu di PT. XYZ - Putri, Indah Septi Yunita; Bakhtiar, Ary; Amir, Nur Ocvanny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
One of the many natural resources in Indonesia is Non-Timber Forest Products (NTFPs). Non-timber forest products include all biological forest products, both vegetable and animal. The leading commodity of NTFPs is semi-finished sap. The resin sap comes from secretions (sap) from the meranti-merantian tribe or Dipterocarpaceae, such as Shorea sp, Vatica sp, and Dryobalanops sp. Stone resin became one of the export commodities with the largest destination, namely India. Stone resin is used as the basic material for making incense. This study aims to determine the potential of stone resin and export prospects at PT. XYZ. This study used qualitative descriptive analysis by presenting tables and graphs. The types of data used are secondary data and primary data. The results showed that the potential of stone resin produced by West Kalimantan's forests is beneficial in export activities. Indian Hindu culture has an impact on increasing the export of stone resin every year at PT. XYZ. This research is expected to contribute to people who want to penetrate the international market in doing business.